Advancing the Assessment and Treatment of Comorbid Pediatric Chronic Functional Abdominal Pain (CFAP) and Restrictive Eating Disorders - Emily A. Beckmann; Claire M. Aarnio-Peterson; Kristen E. Jastrowski Mano (Children, 2023)
The aim of this review is to heighten awareness of the association between chronic functional abdominal pain (CFAP) and restrictive eating disorders (ED) in adolescents. We describe current diagnostic practices and propose future research efforts to improve the assessment and treatment of comorbid CFAP and restrictive EDs. A narrative review of the literature on CFAP and EDs was performed using PubMed, JSTOR, ScienceDirect, and PsycINFO and the following search terms: ‘restrictive eating disorders’, ‘chronic functional abdominal pain’, ‘chronic pain’ ‘treatment’ ‘diagnosis’ and ‘adolescents’. Published studies on restrictive EDs and CFAP from May 2008 to March 2023 were included. Ascribable to the overlap in etiology and symptom presentation, adolescents with chronic pain are significantly less likely to have their ED pathology promptly identified by providers compared to adolescents without comorbid chronic pain. This highlights the importance of the time sensitive and accurate identification of EDs in adolescents with CFAP. Overall, assessment methods are limited and EDs take longer to be identified in adolescents with comorbid CFAP. Future efforts should address diagnostic practices in pediatric settings and improve the communication among medical and mental health providers in order to promote the rapid and effective diagnosis and treatment of comorbid CFAP and EDs.